2018
DOI: 10.1186/s12936-018-2426-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the national policy of single screening and treatment for the prevention of malaria in pregnancy in two districts in Eastern Indonesia: health provider perceptions

Abstract: BackgroundMalaria in pregnancy has devastating consequences for both the expectant mother and baby. Annually, 88.2 (70%) of the 125.2 million pregnancies in malaria endemic regions occur in the Asia–Pacific region. The control of malaria in pregnancy in most of Asia relies on passive case detection and prevention with long-lasting insecticide-treated nets. Indonesia was the first country in the region to introduce, in 2012, malaria screening at pregnant women’s first antenatal care visit to reduce the burden o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 14 publications
0
18
1
Order By: Relevance
“…Other studies had shown the advantages of RDTs including their cost-effectiveness [12,16,41]. A qualitative study had shown that formal providers like nurses had greater trust in microscopy and some doubted whether RDTs gave correct results [42]. The current study did not indicate such issues in context of CHWs carrying out large-scale screening using RDTs.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Other studies had shown the advantages of RDTs including their cost-effectiveness [12,16,41]. A qualitative study had shown that formal providers like nurses had greater trust in microscopy and some doubted whether RDTs gave correct results [42]. The current study did not indicate such issues in context of CHWs carrying out large-scale screening using RDTs.…”
Section: Discussioncontrasting
confidence: 59%
“…The fear of needle prick in IST was not found to be a big barrier. IST was found to be acceptable to pregnant women and providers in Indonesia [42,47]. The acceptability of IST was found to be high where the providers enjoyed trust of community, especially women [27].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Health providers in western Kenya described microscopy as the gold standard, while RDTs were considered useful in settings without laboratories or electricity but had limited sensitivity and specificity [ 14 ]. Lack of trust in negative RDT results prompted some providers to advise re-checking RDT results using microscopy, as found in an evaluation of the SSTp strategy in West Sumba and Mimika [ 21 ]. Provider mistrust was also reported in Uganda, where only 49% of health workers believed a negative result to be true [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 In 2012, Indonesia was the first country in the region to implement a strategy of screening and treating malaria at the first antenatal visit, with passive case management provided thereafter. 7 In The Lancet Infectious Diseases, Rukhsana Ahmed and colleagues 8 report the results of the first IPT study in the WHO South-East Asia region, a three-arm, open-label, cluster-randomised controlled trial in HIV-negative women from Sumba island (site of low malaria transmission) and southern Papua (site of moderate, year-round, malaria transmission), eastern Indonesia. Participants (of any gravidae between 16 and 30 weeks' gestation) received either single screening with a rapid diagnostic test and treatment with dihydroartemisinin-piperaquine if parasitaemic or passive case detection to delivery, intermittent screening with a rapid diagnostic test at each antenatal visit and treatment with dihydroartemisinin-piperaquine if parasitaemic, or IPT with dihydroartemisininpiperaquine at monthly visits without screening.…”
Section: Devising a Strategy For Prevention Of Malaria In Pregnant Womentioning
confidence: 99%